Household self-insurance and the value of disability insurance in the United States - Maxwell Kellogg (Institute for Fiscal Studies (IFS), 2022)
This paper uses a life cycle model to study the welfare implications of reforms to U.S. Disability Insurance (DI) while accounting for household self-insurance. In addition to crowding out the insurance value of DI, household self-insurance may drive negative selection into DI by reducing implicit application costs. Allowing for such interactions, I find that revenue-neutral expansionary DI reforms do not necessarily improve welfare. However, an asset test reduces negative selection and improves the welfare effects of DI expansions. Household self-insurance crowds out the value of DI expansions, but abstracting away from insurance value can still deliver erroneous policy recommendations.
Keywords: 330